Development and validation of the care challenge scale in family caregivers of people with Alzheimer's disease - Sharif Nia, Hamid; Sivarajan Froelicher, Erika; Hosseini, Lida; Ashghali Farahani, Mansoureh; Hejazi, Sima (Frontiers in Public Health, 2022)
Background: Alzheimer’s Disease (AD) is a progressive and debilitating disorder that strongly affects people with AD and their families. The changings in signs of disease and its treatment lead to the challenges in people with AD that affects the performance and the ability of caregivers, the social life, and physical, emotional, and psychological aspects of caregiver’s health. Therefore, this study was designed to develop and validate the Care Challenge Scale (CCS) for family caregivers of people with AD in the care context of Iran. Method: This is a cross-sectional study, the primary scale was based on 14 semi-structured interviews with family caregivers of Iranian people with AD. In the next phase, the psychometric features were assessed including the face validity (qualitative and quantitative), content validity (qualitative and quantitative), item analysis, structural validity (exploratory and confirmatory factor), and construct validity (convergent and discriminant validity). Finally, the reliability was assessed using internal consistency (Cronbach's alpha, Omega-McDonald's coefficient, and the average inter-item correlation), stability (intraclass correlation coefficient), and absolute reliability. Results: The sample size was 435 Iranian family caregivers with mean age of 50.26(±13.24) years who filled out online questionnaires. Based on the results of the qualitative phase, an item pool was generated with 389 items and after deleting overlapping and unrelated items, the CCS with 14 items was created. The results of the quantitative phase showed that the CCS consists of two factors with ten items each that are named effective role-play challenge and lack of social-financial support, they explained 42.23% of the total variance. Furthermore, The results of confirmatory factor analysis showed a good fitness of the scale structure model and it had convergent and discriminant validity. The reliability indexes showed this scale has internal consistency and stability. Conclusion: The most care challenge among Iranian family caregivers of people with AD is effective to role-play challenges and lack of social–financial support. The scale as designed has good validity, internal consistency, and stability that can be used by therapists, nurses, and researchers for the assessment of the challenges of this population.